Comparative analysis of tax capacity in regions of Russia - Parfenova, Lyudmila; Pugachev, Andrey; Podviezko, Askoldas (Technological and Economic Development of Economy, 2016)
Influence of tax policy of the state and its regions is vital for country’s economy; it is the major source of allocation of expenditure obligations of tax capacity on the sub-federal level. The purpose of this research is to estimate the predictive tax capacity of regions (TCR) and to create a comparative evaluation of regions on the basis of criteria, which are influencing the tax capacity using different methods of evaluation: multiple criteria decision-making (MCDM) and econometric methods. Criteria, which are having the greatest influence on the TCR, were identified on the basis of empirical data both using regression analysis and expert estimates. The objective, subjective, and cumulative weights have been calculated, the degree of concordance of expert opinions was gauged. The comparative evaluation of the TCR in four regions of Russia in 2000–2012 was performed on the basis of MCDM methods. First published online: 23 Nov 2016